Developing a Persian Version of the Checklist of Pragmatic Behaviors and Assessing Its Psychometric Properties: A Preliminary Study - Faezeh Koohestani; Parisa Rezaei; Mahboubeh Nakhshab (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Pragmatic assessment is critical because of its effective role in social and academic success. It can provide early intervention if the evaluations are made early in childhood. In this regard, an appropriate tool is necessary for the pragmatic evaluation of preschool children in Iran. The checklist of pragmatic behaviors (CPB) is an observational tool for assessing pragmatics in children aged 3-5 years. This study aims to develop a Persian version of the CPB and evaluate its psychometric properties. Materials & Methods: This is a methodological study conducted in 2018. The participants were 63 children in three age groups of 3, 4, and 5 years selected from kindergartens in Isfahan City, Iran, using a cluster sampling technique. The inclusion criteria were being 3-5 years old and Persian speaker. This study was conducted in two steps; translation and localization of the CPB to Persian and evaluating the validity and reliability of the Persian CPB. The studied variables were 25 pragmatic behaviors mentioned in the CPB. The test-retest reliability was estimated using 15 children (5 from each age group) in a 2-week interval. Scoring was based on the presence (verbal, nonverbal) or absence of the behavior. The internal consistency was estimated using the Cronbach α coefficient; discriminant validity was assessed concerning age, and criterion validity by measuring the CPB's correlation with the ages and stages questionnaire (personal-social subscale) and the behavioral problem questionnaire. Nonparametric tests were used for factor analysis and estimating inter-rater agreement and test-retest reliability. The obtained data were analyzed in SPSS 21 and AMOS applications. Results: The Persian CPB's total score significantly increased with the increase of age (P≤0.001). Factor analysis reported four factors for the Persian CPB. Criterion validity evaluation showed the moderate significant correlation of the CPB (r=0.58) with the personal-social subscale of age and stages questionnaire (ASQ), and its weak negative significant correlation (r=-0.28) with the behavior problem questionnaire. A Cronbach α of 0.83 was obtained for internal consistency, and a correlation coefficient of 0.665 (P=0.007) was reported for test-retest reliability. Conclusion: The Persian version of the CPB has acceptable psychometric properties. The differences in some items of this version compared to other versions may be because of differences in culture and language.